Upaya Meningkatkan Hasil Belajar Matematika Pada Materi Luas Bangun Datar Menggunakan Kombinasi Model Problem Based Learning, Grup Investigasi, Make A Match Pada Kelas IV UPTD SDN 1 Kait-Kait Kabupaten Tanah Laut - Ayu Ispi Ramadani; Susilawaty (CV. ITTC INDONESIA, 2023)
This study aims to describe student learning outcomes using the Problem Based Learning model, Group Investigation, Make A Match in learning activities. This type of research uses Classroom Action Research (PTK) which is carried out in 3 meetings using qualitative and quantitative approaches. The subjects of this study were 20 students in class IV UPTD SDN 1 Kait-Kait in the 2022/2023 academic year. Based on the results of the study it can be interpreted that: (1) Classical teacher activity reaches the criteria of